Fine needle aspiration cytological diagnosis of thyroid nodule with its clinical correlation (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: Nodular goiter is common in Bangladesh. Thyroid nodules are important for their malignant potential especially the solitary and cold ones and when functionally euthyroid. Objectives: This study was designed to investigate the frequency of malignancy and cellular aberration detected by fine needle aspiration cytology (FNAC) in euthyroid nodules and its correlation with clinical findings. Methods: Subjects with nodular goiter attending Endocrine out patient department [n=150, nonpregnant, age (mean± SD): 37±12 years; sex (male: female): 21:129] were recruited for this study. All subjects underwent clinical risk stratification, estimation ofFT4 and TSH as well as ultrnsonogram (USG) and isotope scan of thyroid. Thyroid nodules were categorized into malignant, suspicious, benign and indeterminant on the basis of cellular character by FNAC. Statistical analysis was done by Chi-square and multiple regression analysis. Results: Patients were mostly females (86%) and 4.7% had family history of thyroid problems. Some had recent changes of size (14.7%), pain in the nodule (4%) and dysphagia (6%). Nodules were solitary in 45.3% and the rest (54.7%) had multinodular goiter. Enlarged regional lymph node was found in 12.7% patients. About 41 % were partially-cold followed by cold nodules (26.7%), patchy (16.7%), isoform (12%) and hot (4%) by isotope scan. Frequency of malignant (10%) character was highest in cold nodules followed by uniform (5.6%), patchy (4.0%) and partially cold (1.6%) while none in hot nodules; which were 22.5%, 11.1 %, 4.0%, 9.8% and 16.7% respectively for suspicious nodules. About 17% showed cellular aberration and 4.7% were clearly malignant, whereas 124 (82.7%) were benign. Of the malignant, 4 were solitary and 3 were multinodular; which were 10 and 9 among the suspicious ones. A significant number (77%, 20 out of 26) among the malignant/suspicious nodules fell into moderate to high risk category (x2=22.861, p